Waste management in health establishments during the health emergency (COVID-19) (AACINI - International Journal of Industrial Engineering, 2020)
The work presents the protocol established for the Management of Solid Waste Generated in Health Establishments, in times of Covid-19; Likewise, it also details the actions to be followed in the cases of patients with home isolation and / or A1 or A2 Isolation Centers in the province of Tucumán. The treatment of waste in Health Establishments during the health emergency will broadly follow the same guidelines established in Ministerial Resolution 134/2016, the criteria of which the Province has been meeting. However, during this period some concepts in the treatment of common waste are modified. To date there is no evidence of the risk of infection by the New Coronavirus from waste. However, based on what has been observed for other viruses, it is considered that the residues could pose a risk of infection for people who come into direct contact with them. This protocol for an adequate management of MSW generated during the Sanitary Emergency by (COVID-19) seeks to: protect and prevent contagion through Waste, protect the personnel in charge of the collection of solid urban waste and prevent anyone from contact the waste of a suspected or confirmed coronavirus patient.
Keywords: Coronavirus; Waste; Health Establishments; Solid Urban Waste; Covid-19